Proyecto de factibilidad para la producción y comercialización de ropa para mascotas caninas en la ciudad de Loja. - Medina Capa, Gilson Alexander (2023)
The "Feasibility project for the production and commercialization of clothing for canine pets in the city of Loja"; the idea is to provide consumers with a quality product, taking advantage of existing resources: skilled labor and raw material and thus contributing to socio- economic development, meeting the objectives required for the research study process, we conducted studies to determine its feasibility, using analytical, deductive and inductive methods, as well as survey and interview techniques; the segment chosen for the study were the families of the city of Loja, and we calculated a sample of 382 surveys The market study had an unsatisfied demand of 3,7226 garments per year for the first year. The technical research study determined an installed capacity of 43800 garments and a utilized capacity of 10,400 garments per year; it will have a market share of 28% and will adopt the name of Compañía Unipersonal de Responsabilidad Limitada and will be known as "MASCOTIN" E.U.R.L.; located in the city of Loja. The financial study determined that the investment required would be of 8692.29 dollars for the implementation of the project, which we will finance by 31% in shareholders' equity capital, and 69% in external capital. According to the financial indicators, we obtained a positive net present value of 14,489.23 dollars; the internal rate of return is 68.10%; in the benefit-cost ratio, the profitability of 1.21 dollars, which means that for every dollar invested, we will obtain 0.21 cents of profitability; the capital recovery period will be one year, four months and 20 days; the sensitivity analysis indicates that the project supports an increase in costs of 12.20% with a sensitivity of 1.00, while it will be able to withstand a decrease in income of up to 10.08%, generating a sensitivity of 1.00; for these reasons, we can say that the project is feasible